KERANGKA KONSEPTUAL: PERAN CORE VALUES AKHLAK DALAM MENINGKATKAN KINERJA KARYAWAN - Kusuma, Tatiana; Silvianita, Anita; Rubiyanti, Nurafni; Widodo, Arry (FEB Universitas Sam Ratulangi Manado, 2024)
This study aims to investigate the effect and relationship between organizational culture moderate by core values AKHLAK as the moderating variable and leadership style on employee performance using data from one of the banking companies under BUMN corporate. The method used in this research is a quantitative with data collection techniques through distributing questionnaires. The results showed that organizational culture and leadership style are the most important factor of improving employee performance, followed by core values AKHLAK, which moderate the influence of organizational culture in the company. Core values AKHLAK as a moderating variable that links organizational culture and leadership style on employee performance. This research has several implications for companies in implementing an organizational culture that is moderated by the core values AKHLAK for leaders and employees in order to improve employee performance well. Companies need to build an implement program that can increase the understanding and application of core values AKHLAK as an organizational culture adopted by BUMN, so they can improve employee performance and achieve company goals and targets. Keywords: Core Values AKHLAK, Organizational Culture, Leadership Style, Employee Performance